2003
DOI: 10.1093/emboj/cdg496
|View full text |Cite
|
Sign up to set email alerts
|

CIITA regulates transcription onset viaSer5-phosphorylation of RNA Pol II

Abstract: C.Spilianakis, A.Kretsovali and T.Agalioti contributed equally to this workWe describe the temporal order of recruitment of transcription factors, cofactors and basal transcriptional components and the consequent biochemical events that lead to activation of the major histocompatibility class II (MHCII) DRA gene transcription by IFN-g. We found that the gene is`poised' for activation since both the activators and a fraction of the basal transcriptional machinery are pre-assembled at the enhancer and promoter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
85
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 45 publications
12
85
0
5
Order By: Relevance
“…1A) (29). The assay relies on the fact that the known constituents of the MHCII enhanceosome (RFX, CREB, and NF-Y) bind together in a highly cooperative fashion, such that they assemble into a stable higher order complex on DRA promoter fragments (18,24,29,30). This nucleoprotein complex generates a composite interaction surface to which CIITA binds via multiple synergistic protein-protein contacts (29,(32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) (29). The assay relies on the fact that the known constituents of the MHCII enhanceosome (RFX, CREB, and NF-Y) bind together in a highly cooperative fashion, such that they assemble into a stable higher order complex on DRA promoter fragments (18,24,29,30). This nucleoprotein complex generates a composite interaction surface to which CIITA binds via multiple synergistic protein-protein contacts (29,(32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
“…RFX binds in a highly cooperative manner with two other factors, CREB (22) and NF-Y (23), to their respective X, X2, and Y box target sites (24 -28). This generates a higher order MHCII enhanceosome complex that serves as a landing pad for CIITA (29,30). CIITA is recruited to the enhanceosome via multiple protein-protein interactions with RFX, CREB, and NF-Y (29, 31-35).…”
mentioning
confidence: 99%
“…CIITA interacts with the constitutively expressed DNA-binding transcription factors RFX5, NF-Y, and CREB to assemble a B lymphocyte-specific enhanceosome that regulates MHC class II gene expression (22)(23)(24)(25)(26)86). Spilianakis et al (23) have recently described the temporal recruitment of transcription factors, cofactors, and basal transcriptional components leading to the expression of the MHC class II DR␣ gene by IFN-␥. CIITA is also a potent activator of MHC class I genes, where it is also thought to assemble a B cell enhanceosome.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of DNA-binding transcription factors have been identified that interact with these promoter proximal DNA sequence elements. For example, a B lymphocyte-specific enhanceosome consisting of the coactivator CIITA and DNA-bound transcription factors RFX, CREB/ATF, and NF-Y leads to high cell surface class I and II expression in B lymphocytes (22)(23)(24)(25). CIITA, a transcriptional coactivator that induces both MHC class I and class II genes does not bind DNA directly, but rather depends on factors, such as RFX and CREB/ ATF, that bind to the CRE element (16,20,21).…”
mentioning
confidence: 99%
“…Detection of coimmunoprecipitated DNA was by quantitative real-time PCR. Five microliter of eluted DNA and primers directed against the HLA-DRA promoter (Spilianakis et al, 2003) or the GAPDH promoter (provided in the EZ-ChIP kit) were combined with Reaction Mix (QuantiTect SYBR Green PCR kit; Qiagen Inc.). Data were normalized to the signal detected with non-specific antiserum.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%